2020
DOI: 10.1155/2020/8853314
|View full text |Cite
|
Sign up to set email alerts
|

sEMG-Based Neural Network Prediction Model Selection of Gesture Fatigue and Dataset Optimization

Abstract: The fatigue energy consumption of independent gestures can be obtained by calculating the power spectrum of surface electromyography (sEMG) signals. The existing research studies focus on the fatigue of independent gestures, while the research studies on integrated gestures are few. However, the actual gesture operation mode is usually integrated by multiple independent gestures, so the fatigue degree of integrated gestures can be predicted by training neural network of independent gestures. Three natural gest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 33 publications
(19 reference statements)
0
9
0
Order By: Relevance
“…However, another study showed that the linear and non-linear approaches were equally valid to estimate changes in power loss during a fatiguing repetitive leg extension exercise 12 , 31 . In the present study, non-linear techniques were developed using an MLPNN to combine different time and spectral features of the sEMG signal into a fatigue index representing the estimated changes in power output 12 , 31 , 34 , 35 . The results showed that the estimation errors were smaller when using non-linear mapping of power loss during dynamic contractions compared to linear mapping, as it showed higher SNR and correlation coefficients between the actual and estimated power output in three muscle groups of lower limbs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, another study showed that the linear and non-linear approaches were equally valid to estimate changes in power loss during a fatiguing repetitive leg extension exercise 12 , 31 . In the present study, non-linear techniques were developed using an MLPNN to combine different time and spectral features of the sEMG signal into a fatigue index representing the estimated changes in power output 12 , 31 , 34 , 35 . The results showed that the estimation errors were smaller when using non-linear mapping of power loss during dynamic contractions compared to linear mapping, as it showed higher SNR and correlation coefficients between the actual and estimated power output in three muscle groups of lower limbs.…”
Section: Discussionmentioning
confidence: 99%
“…A multi-layer perception neural network (MLPNN) was chosen to relate changes in sEMG variables and power output because it shows good accuracy to relate sEMG variables and fatigue indices 12 , 31 , 35 . Four sEMG parameters were calculated from each contraction of all of the subjects: (1) MAV is an estimate of the mean absolute value of the signal, as the integrated EMG is divided by the integration time 15 , 34 , 50 ; (2) zero crossing (ZC), as the number of times that the waveform crosses zero, is a simple measure of the main frequency of the signal 15 , 34 , 50 ; (3) slope sign change (SSC), as the number of times that the slope of the waveform changes sign, provides another measure of frequency content 15 , 34 , 50 ; and (4) wavelength (WL) provides information on the waveform complexity in each segment 15 , 34 , 50 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…They are a special type of RNN that attempts to solve the vanishing gradient problem and is widely used in sEMG control like performing models for myoelectric based control of a prosthetic hand, [8][9][10] neural interface toward intuitive prosthetic control for amputees, 11 control of a hybrid dynamical transfemoral prosthesis, 12 prediction model of gesture, and dataset optimization. [13][14][15] Deep learning techniques involve large neural networks and achieve state-of-the-art output pattern recognition accuracy. This is done in two stages: in the learning phase, a classifier is created based on the input signal (sEMG) and output value to determine which signal belongs to.…”
Section: Introductionmentioning
confidence: 99%
“…To address this issue, long‐short term memory (LSTM) networks have been developed. They are a special type of RNN that attempts to solve the vanishing gradient problem and is widely used in sEMG control like performing models for myoelectric based control of a prosthetic hand, 8–10 neural interface toward intuitive prosthetic control for amputees, 11 control of a hybrid dynamical transfemoral prosthesis, 12 prediction model of gesture, and dataset optimization 13–15 …”
Section: Introductionmentioning
confidence: 99%